Sosialisasi Keamanan Perjalanan Kereta Api: (Studi Kasus Perlintasan JPL 78 Stasiun Bekasi) - Mulyani, Haniva; Nugroho, Agus; Nugroh, Sinung Tri; Gaputio, Iqshan Altemawi; Nugraha, Alisha Aisyah; Milliaran, Milliaran (Institut Transportasi dan Logistik Trisakti, 2024)
The security and safety of the public and the drivers of users of railway crossings and also the security of train travel, it is necessary to hold socialization to the community. Socialization is carried out to displace people who often violate regulations, which can put the safety and security of train trips and also motorists at risk. People who pass by must obey the regulations that have been made. Because if you violate it, in addition to being subject to sanctions, it can also endanger motorists or road users who pass by and also endanger train travel and passengers who use the train service. Most of the people around the Bekasi Station crossing are still not disciplined, both in personal safety on the crossing route and discipline in implementing health protocols. Evidenced by data that shows that the number of violations is relatively high. Preventive and persuasive measures are carried out so that the public is easier to receive the information submitted, but if the level of discipline of the community and road user motorists at the railway crossing is still low, it is necessary to take strict action taken by the relevant agencies in order to maintain public security and safety and smooth travel of the train. It is hoped that from the socialization that has been carried out, the community can be more aware of the importance of obeying the applicable regulations in the direction and also the regulations around the crossing of a plot. In order to maintain safety in driving and the safety of train travel.